Measuring Consumers' Continuance Usage Intention to Use Airline Websites in Saudi Arabia - Humera Khan; Faouzi Ayadi; Muhammad Tanveer (Qubahan Academic Journal)
Airline websites are the major online channel to provide quality services to their consumers. The main objective of this study is to analyze the factors which impact on consumers continuance intention to use airline websites in Saudi Arabia. A theoretical framework has been proposed using information system literature to check the continuance intention of consumers in the context of airline websites. The study implies the statistical tests and regression analysis approach to check the model’s robustness. A theoretical model is proposed and hypotheses are developed to check the impact of perceived usefulness, satisfaction, confirmation, system quality and information quality on consumers continuance intention to use airline websites. Data was collected by administering a questionnaire and a valid response from 305 consumers was used in the analysis. Statistical tests are performed using SPSS and AMOS. The results of regression analysis show the profound impact of perceived usefulness, confirmation, satisfaction, service quality and information quality on the continuance intention to use the airline website. The results also confirm that consumers are willing to continuously use the airline websites if they found it easy to use and provide them all available services with high quality and data accuracy. This enhances the confirmation of consumers intents to use the airlines websites before they get the actual satisfaction after using it. This research gives theoretical confirmation and practical implications to airlines to design their websites. By inspecting the factors that positively contribute most in consumers’ willingness to continuously use airline websites, the research enhances both theoretical and practical improvements in the field of information system continuance acceptance rather than one time use of new systems only. For airline industry this gives an insight to improve the strategies to provide useful and quality information to the consumers to continuously use their websites.